THE STRATEGIES APPLIED BY EFL LEARNERS TO OVERCOME MORPHO-SYNTACTIC DEVIATION IN SECTION 2 OF TOEFL TEST IN A PESANTREN-BASED UNIVERSITY - Abdur Rofik (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
The study aims at revealing the morphological and syntactical deviations patterned by EFL students, and their strategies to respond structure and written expression of TOEFL-Like Test. 70 students participated in this study. The students who were from study programs of English Literature, Technical Information, and Political Sciences of Universitas Sains Alqur’an were involved in this study. Their feedback were analyzed based on a qualitative approach. The findings exposed that 70 test-takers constructed 1.711 morpho-syntactic deviations. The most six morpho-syntactic problematic queries based on EFL students’ responses are epithet in parallel structure, subject-verb needs, object needs in noun phrase forms, quantifier-noun agreement, inversion of negative expression, connector subject pronoun in the adjective clause. Concerning strategies adopted by the students, they revealed that paying to the object of the preposition, focusing on past participles, making in mind that verbs of the sentence agree to the subject in cases of prepositional phrases, making in mind verbs agreement on an expression of quantity cases, and focusing on the present participle questions need to be put in. Furthermore, this study suggested that the EFL students are encouraged to take into consideration those six most morpho-syntactic deviations.